GE_GERICHTE P/143/1999 vom 19. Dezember 2013 - GE Cour de justice (2013)
ADMINISTRATION DES PREUVES; PREUVE; HOMICIDE; MEURTRE; ASSASSINAT; MEURTRE PASSIONNEL; LÉGITIME DÉFENSE; FIXATION DE LA PEINE; TORT MORAL | CPP.389; CPP.331; aCP.33; CP.2.1; CP.2.2; CP.49.9; CP.47; CP.111; CP.112; CP.113; CO.47